Yield and Quality of Brassica Cultivars as Affected by Soil Salinity - Mahmood, I.A.; Ali, A.; Shahzad, A.; Salim, M.; Jamil, M.; Akhtar, J. (Biological Sciences - PJSIR, 2007)
. A field study was conducted at two different salt-affected locations (1) district Hafizabad having electrical cond uctivity of soi l extract (ECe) = 6.46 dS/m and sodium absorption ratio (SAR) = 7.22 and (2) district Sargodha (ECe = 13.02 dS/m ; SAR = 12.70) to test the yield response and quality of five brassica cultivars. The cultivars viz. sultan raya, BRS-II , rainbow, shiralle and dunkled were selected after preliminary screening against NaCl salt stress under hydroponic conditions. Basal dose of NPK was applied at the time of sowing. Growth and yield parameters i.e., plant height, number of branches, number of pods per plant and seed yield were compared . The rainbow and dunkled cultivars showed maximum plant height at both the sites while sultan raya and BRS-Il produced more number of branches as compared to rest of the cultivars. Among all the cultivars, although, sultan raya out yielded on the basis of seed yield (1446 and 869 kg/ha) at site-I and site-2, respectively, but there was about 40% decrease in seed yield at site-2 due to high salinity (13.02 dS/m) followed by BRS-II which showed about 45% yield reduction at the same site. Maximum oil contents were determined in the seeds of sultan raya followed by BRS-II and dunkled grown at both the sites. Generally, sultan raya maintained significantly high level of K+ and less Na+ in their tissues grown at both the sites. Overall, Brassica cultivar sultan raya showed promisin g results and better performance than rest of the cultivars at both the sites but there was a significant reduction in growth and yield of all cultivars at site-2 due to higher salinity.